2000
DOI: 10.2136/sssaj2000.641235x
|View full text |Cite
|
Sign up to set email alerts
|

Use of 15N‐Labeled Soil in Measuring Nitrogen Fertilizer Recovery Efficiency in Transplanted Rice

Abstract: In transplanted flooded rice (Oryza sativa L.) culture in Asia, N fertilizer recovery efficiency (RE) estimates are usually greater with the difference method than with the 15N method. These reported differences are greater and more common for transplanted irrigated rice than for upland crops and might be associated with basal N applications when plant demand is low. Added N interactions (ANI), or greater soil N accumulation in fertilized plants than in unfertilized plants, are often cited as the reason for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
3
28
2
4
Order By: Relevance
“…Fageria & Baligar (2001) relataram que a cultivar Metica 1 produziu 23 kg de grãos por quilograma de N aplicado. Dobermann et al (2000) relataram que, com a aplicação de 150 kg ha -1 de N, a eficiência agronômica da cultivar de arroz irrigado IR 72 foi de 20 kg de grãos por quilograma de N aplicado. Yoshida (1981) relatou que a eficiência agronômica nas regiões tropicais, geralmente, situa-se na faixa de 15 a 25 kg de arroz produzido por quilograma de N aplicado.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Fageria & Baligar (2001) relataram que a cultivar Metica 1 produziu 23 kg de grãos por quilograma de N aplicado. Dobermann et al (2000) relataram que, com a aplicação de 150 kg ha -1 de N, a eficiência agronômica da cultivar de arroz irrigado IR 72 foi de 20 kg de grãos por quilograma de N aplicado. Yoshida (1981) relatou que a eficiência agronômica nas regiões tropicais, geralmente, situa-se na faixa de 15 a 25 kg de arroz produzido por quilograma de N aplicado.…”
Section: Resultsunclassified
“…Fageria & Baligar (2001) Fageria et al (2003a) relataram que a eficiência de utilização do N, pela cultura do arroz irrigado, é baixa, em conseqüência das perdas por volatilização, imobilização, lixiviação e desnitrificação. A maioria dos trabalhos realizados mostra que a eficiência de recuperação de N, na cultura do arroz irrigado, situase entre 20 e 40% (De Data et al, 1988;Schnier, 1994;Bronson et al, 2000).…”
Section: Resultsunclassified
“…All plant and soil samples were fine-ground to <0.15 mm prior to N content analyses. N-total and atom% 15 N analyses were done with an automated C-N analyzermass spectrometer (ANCA-MS) similar to that described by Bronson et al (2000).…”
Section: Measurements and Calculationsmentioning
confidence: 99%
“…Most of previous investigations (Bronson et al 2000, Ebid et al 2008) focused on plains where N loss occurred in runoff through interflow leaching and few studies have looked into sloping lands where N loss was reported in runoff through interflow, surface runoff and its erosive sediment. This investigation took interflow and surface-flow into consideration, which may lead to an adequacy in comprehensively studying the nitrogen losses of farmlands.…”
Section: Resultsmentioning
confidence: 99%